Long-term outcomes of urinary tract infection (UTI) in childhood: The LUCI study. (8th November 2019) - Hughes, Kathryn; Cannings-John, Rebecca; Jones, Hywel; Lugg-Widger, Fiona; Lau, Mandy; Paranjothy, Shantini; Francis, Nick; Hay, Alastair; Butler, Christopher; Voort, Judith Van der; Hood, Kerenza
No abstract available